1)Упростить выражение
a) cos^2*(pi+t)+cos^2*(pi-t)
б) sin*(pi/2-t)*tg*(-t)
cos(pi/2+t)
2)Решите уравнение
cos*(2pi-t)-sin*(3pi/2+t)=1

1

Ответы и объяснения

  • IOriOnI
  • почетный грамотей
2012-05-17T19:14:10+04:00

1)

a) cos^2*(pi+t)+cos^2*(pi-t) = cos^2t+cos^2t = 2cos^2t

б) sin*(pi/2-t)*tg*(-t)  /  cos(pi/2+t)

sin*(pi/2-t) = cost

tg*(-t) = -tgt

sin*(pi/2-t)*tg*(-t)= cost*(-tgt) = -sint

cos(pi/2+t) = -sint

sin*(pi/2-t)*tg*(-t)  /  cos(pi/2+t) = -sint / -sint = 1

 

2)  cos*(2pi-t)-sin*(3pi/2+t)=1

cos*(2pi-t) = -cost

sin*(3pi/2+t) = -cost

-cost+cost = 1

0 = 1 - нет  => нет решений